2024
DOI: 10.3390/s24030767
|View full text |Cite
|
Sign up to set email alerts
|

Process Algebraic Approach for Probabilistic Verification of Safety and Security Requirements of Smart IoT (Internet of Things) Systems in Digital Twin

Junsup Song,
Sunghyun Lee,
Dimitris Karagiannis
et al.

Abstract: Process algebra can be considered one of the most practical formal methods for modeling Smart IoT Systems in Digital Twin, since each IoT device in the systems can be considered as a process. Further, some of the algebras are applied to predict the behavior of the systems. For example, PALOMA (Process Algebra for Located Markovian Agents) and PACSR (Probabilistic Algebra of Communicating Shared Resources) process algebras are designed to predict the behavior of IoT Systems with probability on choice operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…• The communication and movements of IoT devices can be represented by τ and δ actions in algebra, respectively [11]; • The decision and risk can be presented by nondeterministic choice operations with probability in algebra, respectively [11].…”
Section: Process Algebra In Digital Twins For Smart Citiesmentioning
confidence: 99%
See 4 more Smart Citations
“…• The communication and movements of IoT devices can be represented by τ and δ actions in algebra, respectively [11]; • The decision and risk can be presented by nondeterministic choice operations with probability in algebra, respectively [11].…”
Section: Process Algebra In Digital Twins For Smart Citiesmentioning
confidence: 99%
“…In addition, as a result of the verification, in case of the probabilistic requirements not being satisfied, it was shown, as a feasibility ground, that the probabilities making the decisions were enhanced at some arbitrarily high level so that the requirements were to be satisfied. The detailed steps of the approach in the previous research are as follows [11]; note that each step is indicated with the numbers from the figure:…”
Section: Previous Research On Probabilitiesmentioning
confidence: 99%
See 3 more Smart Citations